2021
DOI: 10.1155/2021/6692752
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Work-Related Quality of Life and Job Satisfaction in Iranian Occupational Therapists

Abstract: Objective. This study is aimed at exploring the relationship between the work-related quality of life and job satisfaction among Iranian occupational therapists. Methods. In an analytical-descriptive, cross-sectional study, 322 occupational therapists were recruited through a convenient sampling. Inclusion criteria consisted of age between 22 and 50 years, at least one-year work experience, 24 hours of working per week as an occupational therapist, and membership of Iranian Occupation Therapy Association. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Three (3) of the test items (7, 9, and 19) were reversely scored. The tool is validated globally [34], and all the studies that have used it have reported an acceptable Cronbach's alpha value between 0.88 and 0.95 [34][35][36][37][38][39][40].…”
Section: Methodsmentioning
confidence: 99%
“…Three (3) of the test items (7, 9, and 19) were reversely scored. The tool is validated globally [34], and all the studies that have used it have reported an acceptable Cronbach's alpha value between 0.88 and 0.95 [34][35][36][37][38][39][40].…”
Section: Methodsmentioning
confidence: 99%
“…Mendes and Pereira [52] reported a value of 3.40 in the general Portuguese working population, suggesting that healthcare workers may have lower WRQoL. Pre-pandemic, within the AHPs, one study reported WRQoL scores of 82.92 (14.17) for occupational therapists in Iran [53] while another study of Vietnam's healthcare professionals reported higher scores of 95.52 and 92.10 during the pandemic [54], suggesting that these professionals had higher WRQoL than UK-based respondents. However, during the pandemic, lower scores have been reported amongst nurses in hospitals in Iran [55,56], suggesting that country of work and different working practices could influence total WRQoL.…”
Section: Main Messages In Comparison With the Literaturementioning
confidence: 99%
“…In a study by Scanlan et al (2021), 11 out of 14 (79%) occupational therapists in the multidisciplinary team were satisfied with working in mental health. Rostami et al (2021) found that occupational therapists were moderately satisfied with their job. In another study, the majority of participants working in mental health were very satisfied or somewhat satisfied with their jobs (Hayes et al, 2008).…”
Section: Discussionmentioning
confidence: 98%